Row spacing and seeding rate on some agronomic characteristics off rapessed - Santos, Henrique Pereira dos; Bonetti, Luiz Pedro; Silva, Maria Isabel da; Barni, Nídio Antonio (Pesquisa Agropecuaria Brasileira, 2014)
For three years, from 1980 to 1982, at several locations in Rio Grande do Sul State. Brazil, the effect of row spacing and seeding rate on some agronomic characteristics of rapessed (Brassica napus L. var. oleifera Metzg.) was evaluated. Locations, year and seeding rate were the main factors influencing yields of rapeseed. Pooling the date by year showed a significant effet of seeding rate on yields; the highest yields were observed under the lowest seeding rate. There was no significant effect of row spacing but there was asignificant interaction with locations and years.
Keywords: Brassica napus var. oleifera; grain yield.